Amines Mimic Insulin In Vitro and In Vivo: Acceleration of Cellular Glucose Consumption - Sorimachi, Kenji (New Advances in Medicine and Medical Science Vol. 2, 2023)
The present study has been designed to develop new anti-diabetes drugs. Defects in insulin secretion in vivo lead to hyperglycemia, type 1 diabetes mellitus (DM), and either insufficient insulin secretion or insulin resistance, which induces type 2 DM. Although several anti-type 2 DM drugs are available, to our knowledge, anti-type 1 DM drugs have not been developed. Amines have been studied as candidate drugs against type 1 DM, because other basic compounds, such as carbonates (NaHCO3 and NaCO3), accelerate glucose consumption in cultured cells. We evaluated more than 20 chemical compounds, including pharmacological drugs, in cultured cells. Among these, 2-amino-1-phenylethanol (2-A-1-PET) and 2-amino-N-cyclohexylethanol (2-A-N-CET) significantly accelerated glucose consumption, which was followed by lactate production in cells. Moreover, treatment with 2-A-1-PET reduced glucose levels in rats. In cells, both 2-A-1-PET and 2-A-N-CET abolished the effects of DM-inducing drugs, such as streptozotocin and alloxan, and nicotinamide, on glucose consumption, whereas both 2-A-1-PET and 2-A-N-CET exerted additive effects with vanadium, carbonates, or concanavalin A on glucose consumption.